2024
DOI: 10.1039/d3ta06875g
|View full text |Cite
|
Sign up to set email alerts
|

Ni3Se4/Fe(PO3)2/NF composites as high-efficiency electrocatalysts with a low overpotential for the oxygen evolution reaction

Ting-Yu Shuai,
Qi-Ni Zhan,
Hui-Min Xu
et al.

Abstract: The design of efficient, environmentally friendly, stable and low-cost oxygen evolution electrocatalyst is the technical difficulty to realize the commercial application of water electrolysis. Here, we have developed a novel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…For the HER, FeO x N y accelerates the adsorption and dissociation of water, while Mo 2 N accelerates the desorption of H 2 , causing better activity than one-component heterostructures. 172 For example, Shuai et al 173 combined the high crystallinity Ni 3 Se 4 with high conductivity but poor activity and the low crystallinity Fe(PO 3 ) 2 with poor conductivity but abundant defects; the crystalline phase optimized the charge transfer ability, and the amorphous phase provided more active sites and achieved OER activity that was far superior to that of a single component.…”
Section: Discussionmentioning
confidence: 99%
“…For the HER, FeO x N y accelerates the adsorption and dissociation of water, while Mo 2 N accelerates the desorption of H 2 , causing better activity than one-component heterostructures. 172 For example, Shuai et al 173 combined the high crystallinity Ni 3 Se 4 with high conductivity but poor activity and the low crystallinity Fe(PO 3 ) 2 with poor conductivity but abundant defects; the crystalline phase optimized the charge transfer ability, and the amorphous phase provided more active sites and achieved OER activity that was far superior to that of a single component.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Hydrogen production by water electrolysis is an emerging and promising method. 3,4 However, oxygen evolution reaction (OER) has some inherent disadvantages, including slow kinetics, high theoretical potential (1.23 V vs RHE), and uneconomical products, which hinder the widespread adoption of this method. 5−7 To overcome these limitations, researchers have been exploring the urea oxidation reaction (UOR) with a theoretical voltage of only 0.37 V vs RHE to break bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing carbon dioxide emissions is crucial for achieving sustainable development. , Hydrogen production by water electrolysis is an emerging and promising method. , However, oxygen evolution reaction (OER) has some inherent disadvantages, including slow kinetics, high theoretical potential (1.23 V vs RHE), and uneconomical products, which hinder the widespread adoption of this method. To overcome these limitations, researchers have been exploring the urea oxidation reaction (UOR) with a theoretical voltage of only 0.37 V vs RHE to break bottleneck. , Numerous studies have shown that UOR does not impede the generation of H 2 during water electrolysis. Furthermore, when UOR is applied to seawater electrolysis, it can prevent the competition of chlorine evolution reaction and broaden the potential selection range for the hydrogen evolution reaction (HER) .…”
Section: Introductionmentioning
confidence: 99%